Electromyographic study of the ragidospasticity of athetosis. Issue 1 (February 1973) - Andrews, Colin J.; Neilson, Peter; Knowles, L.
Abstract : The static and dynamic components of the tonic stretch reflex and shortening reactions have been studied in 10 patients with athetosis. EMG activity could be recorded only from the biceps muscle when the patient was at rest. The dynamic stretch reflex increased with the velocity of stretching in all muscles examined except the biceps. The biceps stretch reflex was found to be inhibited by increasing muscle length, whereas the stretch reflexes of triceps, hamstrings, and quadriceps muscles were facilitated by increasing muscle length. Reinforcement increased resting activity in the biceps and the dynamic shortening reaction of the triceps muscle. Both these effects were suppressed by the action of phenoxybenzamine. Although phenoxybenzamine was shown to reduce muscle tone in a double-blind controlled trial, no corresponding improvement was detected in involuntary movements or the patients' performance in a tracking test. The differences between the pattern of hypertonus in athetosis, Parkinson's disease, spasticity, and activated normal subjects are presented in discussion.